American College of Cardiology/American Heart Association (ACC/AHA) Class I Guidelines for the Treatment of Cholesterol to Reduce Atherosclerotic Cardiovascular Risk: Implications for US Hispanics/Latinos Based on Findings From the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Issue 5 (May 2017) - Qureshi, Waqas T.; Kaplan, Robert C.; Swett, Katrina; Burke, Gregory; Daviglus, Martha; Jung, Molly; Talavera, Gregory A.; Chirinos, Diana A.; Reina, Samantha A.; Davis, Sonia; Rodriguez, Carlos J.
Abstract : Background: The prevalence estimates of statin eligibility among Hispanic/Latinos living in the United States under the new 2013 American College of Cardiology/American Heart Association (ACC/AHA) cholesterol treatment guidelines are not known. Methods and Results: We estimated prevalence of statin eligibility under 2013 ACC/AHA and 3rd National Cholesterol Education Program Adult Treatment Panel (NCEP/ATP III) guidelines among Hispanic Community Health Study/Study of Latinos (n=16 415; mean age 41 years, 40% males) by using sampling weights calibrated to the 2010 US census. We examined the characteristics of Hispanic/Latinos treated and not treated with statins under both guidelines. We also redetermined the statin‐therapy eligibility by using black risk estimates for Dominicans, Cubans, Puerto Ricans, and Central Americans. Compared with NCEP/ATP III guidelines, statin eligibility increased from 15.9% (95% CI 15.0–16.7%) to 26.9% (95% CI 25.7–28.0%) under the 2013 ACC/AHA guidelines. This was mainly driven by the ≥7.5% atherosclerotic cardiovascular disease risk criteria (prevalence 13.9% [95% CI 13.0–14.7%]). Of the participants eligible for statin eligibility under NCEP/ATP III and ACC/AHA guidelines, only 28.2% (95% CI 26.3–30.0%) and 20.6% (95% CI 19.4–21.9%) were taking statins, respectively. Statin‐eligible participants who were not taking statins had a higher prevalence of cardiovascular risk factors compared with statin‐eligible participants who were taking statins. There was no significant increase in statin eligibility when atherosclerotic cardiovascular disease risk was calculated by using black estimates instead of recommended white estimates (increase by 1.4%, P =0.12) for Hispanic/Latinos. Conclusions: The eligibility of statin therapy increased consistently across all Hispanic/Latinos subgroups under the 2013 ACC/AHA guidelines and therefore will potentially increase the number of undertreated Hispanic/Latinos in the United States.